Building and Standardizing Crises Administration Scale for Sport Activities from Physical Educators in Baghdad Bureaus - Salman, Muhaned; Mahmood, Shaker (Journal of Physical Education, 2021)
Crises are unpleasant and leads to great loses in physical activities. These crises are without doubt major obstacle in the way of improving these activities thus these crises should be faced and administrated. The research aimed at constructing a scale for crisis administration and concluding standard levels and degrees. The researchers used the descriptive method on (1304) physical educators in Baghdad bureaus and the subjects were (749). The data was collected and treated to conclude a scale for crisis administration and the possibility of applying this scale on the subjects. Finally, the researchers recommended the necessity of using the crisis administration scale as well as making similar studies on other subjects.